2012
DOI: 10.1128/jcm.06576-11
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Commercial Reverse Line Blot Assays for Human Papillomavirus Genotyping

Abstract: The performance of three line blot assays (LBAs), the Linear Array HPV genotyping assay (LA) (Roche Diagnostics), INNO-LiPA HPV Genotyping Extra (LiPA) (Innogenetics), and the reverse hybridization assay (RH) (Qiagen), was evaluated using quantitated whole genomic human papillomavirus (HPV) plasmids ( T he introduction of human papillomavirus (HPV) vaccines has highlighted the need for standardized accurate HPV genotyping assays to ensure comparability of results in laboratories worldwide, both before and afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 10 publications
(8 reference statements)
0
19
0
1
Order By: Relevance
“…The genotyping assays used today differ in their analytical performances with regard to type-specific sensitivities and specificities. Several studies have compared different HPV typing assays to assess their performances in screening and epidemiology using clinical samples (3)(4)(5). However, evaluations of assay performance in different laboratories need to be performed in a standardized manner, such that different assay performance measures can be evaluated and the results can be compared over time against a known and accepted standard (4).…”
mentioning
confidence: 99%
“…The genotyping assays used today differ in their analytical performances with regard to type-specific sensitivities and specificities. Several studies have compared different HPV typing assays to assess their performances in screening and epidemiology using clinical samples (3)(4)(5). However, evaluations of assay performance in different laboratories need to be performed in a standardized manner, such that different assay performance measures can be evaluated and the results can be compared over time against a known and accepted standard (4).…”
mentioning
confidence: 99%
“…Urine samples tested by the TrDNA HPV capillary electrophoresis test had high concordance with corresponding cervical and urine samples tested by the widely used linear array HPV genotyping test (51). However, the TrDNA capillary electrophoresis HPV test is not quantitative, can only detect the presence or absence of hrHPV and, similar to previously published urinebased HPV tests, has limited specificity.…”
Section: Discussionmentioning
confidence: 53%
“…To examine the hrHPV genome in urine ccfDNA, we developed custom dualsequence capture baits to enrich samples for hrHPV DNA from 12 high-risk types (HPV16, 18,31,33,35,39,45,51,52,56,58, and 59). We used liquid-based sequence capture baits to measure the hrHPV genome in urine ccfDNA from women with and without cervical premalignant lesions.…”
Section: Patient Samplesmentioning
confidence: 99%
“…The commercial tests are too expensive though those two kits have plus and minus points. Several studies around the world has showed that linear assay 1 we used has a good performance and is sensitive (Wong et al, 2010;Steinau et al, 2012), hence this test is costly and need a especial PCR machine which is gold plated to get a good reliable result. In low-and medium-resourced countries where the PCR machines are scarce this assay cannot be performed.…”
Section: Discussionmentioning
confidence: 99%
“…GF and LA showed significant discrepancy in detecting HPVgenotypes 39, 52, 26, 66, and 11. More sensitive detection of HPV52 by GF offers an advantage in regions where HPV52 is more prevalent (Wong et al, 2012), hence, linear assay 1 has an advantage for internationally comparable genotyping studies (Steinau et al, 2012).…”
Section: Discussionmentioning
confidence: 99%